2015
DOI: 10.3329/bjz.v41i2.23324
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture practices in two seasonal floodplains of Bangladesh

Abstract: A comparative technical and economic analysis of two communitybased seasonal floodplains (Khirai and Angrail) of Daudkandi Upazila, Comilla during 2008 to 2010, are represented in this paper. The two floodplains differed mainly in management and fish production which were related to capital investment, variable cost, share of profits and proportional reimbursement to the fishers. Local management committees have been developed in each floodplain with significant differences. Average 142 kg/ha of fish fingerlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The weight gain (gm) of species were found T 1 (Rohu: 1250.10±30.10, Catla: 1210.10±30.23, Mrigal: 1201.70±31.75, Silver carp: 1270) significantly (P<0.05) higher than T 2 and T 3 . The contribution of tilapia, an invasive species, was highest in the Khirai floodplain (36.40%), Hypophthalmichthys molitrix comes next (16.89%) (Akter et al, 2013). While catla (3.07%), bata (0.63%), and kalibaus (0.18%) donated relatively slight to the overall fish production, the carp species rohu and mrigal made only small contributions (6.13% and 8.03%, respectively) (Akter et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The weight gain (gm) of species were found T 1 (Rohu: 1250.10±30.10, Catla: 1210.10±30.23, Mrigal: 1201.70±31.75, Silver carp: 1270) significantly (P<0.05) higher than T 2 and T 3 . The contribution of tilapia, an invasive species, was highest in the Khirai floodplain (36.40%), Hypophthalmichthys molitrix comes next (16.89%) (Akter et al, 2013). While catla (3.07%), bata (0.63%), and kalibaus (0.18%) donated relatively slight to the overall fish production, the carp species rohu and mrigal made only small contributions (6.13% and 8.03%, respectively) (Akter et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of tilapia, an invasive species, was highest in the Khirai floodplain (36.40%), Hypophthalmichthys molitrix comes next (16.89%) (Akter et al, 2013). While catla (3.07%), bata (0.63%), and kalibaus (0.18%) donated relatively slight to the overall fish production, the carp species rohu and mrigal made only small contributions (6.13% and 8.03%, respectively) (Akter et al, 2013). The average survival rate (%) species were found T 1 (55) significantly (P<0.05) higher than T 2 (46.67) and T 3 (46.67).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it may also provide directions for the future improvements. Previously, a handful of studies (Mustafa and Brooks, 2009;Akter et al, 2015) compared the performance of various seasonal aquaculture enterprises, including FPAs of this management approach. However, these studies mainly compared aquaculture practices found in different kind of floodplains with different management approaches.…”
Section: Introductionmentioning
confidence: 99%